3D graphene/ carbon nanotubes/ polydimethylsiloxane composites as high-performance electromagnetic shielding material in X-band. (February 2020) - Jia, Hui; Kong, Qing-Qiang; Liu, Zhuo; Wei, Xian-Xian; Li, Xiao-Ming; Chen, Jing-Peng; Li, Feng; Yang, Xiao; Sun, Guo-Hua; Chen, Cheng-Meng
Graphical abstract: High-performance electromagnetic shielding materials are highly desired because radiation and interference problems of electronic equipment. Based on this, a conductive 3D graphene/MWCNTs foam obtained by carbonization from 1200 to 2800 °C is used as the skeleton to make foam/PDMS flexible electromagnetic shielding. The optimal electromagnetic interference shielding effectiveness (EMI SE) is up to 54.43 dB in X-band, and the absorption efficiency reaches to 91.44%. Finally, the relationship between EMI SE and thermal reduction temperature is established. Abstract: High-performance electromagnetic shielding materials are highly desired due to the radiation and interference problems of electronic equipment. In this work, a flexible graphene/multi-walled carbon nanotubes (MWCNTs)/Polydimethylsiloxane (PDMS) electromagnetic shielding composite is fabricated with 3D graphene/MWCNTs foam as electrical conductive skeleton. The structure and composition evolution of foams are studied during the carbonization process from 1200 to 1600 °C and the graphitization of ultra-high temperature (2800 °C). With the removal of functional groups, the repair of defects enhances the ohmic loss while the polarization loss is reduced. An optimal electromagnetic interference shielding effectiveness (EMI SE)is found with an EMI SE of 54.43 dB at 1400 °C. Moreover, compared to pure PDMS, the thermal conductivity of the composites is increased by 193% and the compressive strength is improved from 1.40 MPa to 1.94 MPa. This contribution provides a guidance for designing high-performance carbon-based electromagnetic shielding materials.